2017
DOI: 10.19044/esj.2017.v13n24p416
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Fractures in a Tropical Country

Abstract: Introduction: The increasing number of vehicles and the proliferation of two-wheeled vehicles accentuate the frequency of fractures in our country. The aim of this study is to describe the epidemiology of fractures in Cotonou. Materials and Methods: This prospective two-year study focused on all patients admitted to the emergency department of the National Teaching Hospital of Cotonou for a fracture injury. Results: 1794 fractures were collected in 1432 patients. Fractures accounted for 24.9% of surgical emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…A similar observation was made in a study conducted in Benin, a West African country by Chigblo et al (15) where the majority of fractures occurred in individuals under 50 years old, primarily due to motor traffic crash incidents. This corresponds to our study findings because, in both of the settings, young men tend to use motorcycles as their means of transport to and from work.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A similar observation was made in a study conducted in Benin, a West African country by Chigblo et al (15) where the majority of fractures occurred in individuals under 50 years old, primarily due to motor traffic crash incidents. This corresponds to our study findings because, in both of the settings, young men tend to use motorcycles as their means of transport to and from work.…”
Section: Discussionsupporting
confidence: 81%
“…A study by Curtis et al (16) in the UK found the majority of femur fractures occurred in men in their second and third decades, which aligns with our study findings. However, their study also revealed a bimodal distribution, indicating a second peak in older women, a common finding in many other studies (3,15,(17)(18). In contrast, our study did not observe this second peak among older women.…”
Section: Discussionsupporting
confidence: 54%
“…Les traumatismes des membres constituent un problème de santé publique et sont en augmentation à cause du développement du trafic routier [ 4 ]. Une étude béninoise a montré que 14 % des urgences chirurgicales sont des traumatismes des membres et qu’ils représentent 25 % des admissions en chirurgie [ 4 ].…”
Section: Discussionunclassified
“…8 The functional outcome evaluated according to the criteria of the Mayo elbow performance score (Table 1), it was excellent (90-100 points), good (89-75 points), average (60-74 points) or poor (less than 60 points). 9 Likewise, patients' impressions were based on their level of satisfaction.…”
Section: Methodsmentioning
confidence: 99%